Factors associated with hypertension in pregnant women - Hasya Fariha; Rd Halim; Ashar Nuzulul Putra; Marta Butar Butar (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Hypertension in pregnancy is a major cause of maternal and neonatal morbidity and mortality, and is estimated to contribute to 10–22% of maternal deaths worldwide. The Simpang IV Sipin Community Health Center recorded the highest number of cases of hypertension in pregnancy in the city of Jambi in 2024, with a prevalence of 8%. Purpose: To analyze the relationship between age, parity, history of hypertension, nutritional status (BMI), and stress levels with the incidence of hypertension in pregnant women. Method: This study used an analytical observational research design through a case-control approach with a sample size of 80 people, consisting of 40 case samples and 40 control samples in the working area of the Simpang IV Sipin Community Health Center in Jambi City in 2025. Data analysis included univariate analysis with frequency distribution and bivariate analysis using the Chi-Square test. Results: The study showed that there was no significant relationship between age (p = 0.138) and parity (p = 0.101). Meanwhile, a history of hypertension (p = 0.001), nutritional status (BMI) (p = 0.040), and stress levels (p = 0.000) were significantly associated with the incidence of hypertension in pregnant women. Conclusion: There is a significant relationship between a history of hypertension, nutritional status (BMI), and stress levels. However, age and parity are not significantly related to the incidence of hypertension in pregnant women. Suggestion: It is recommended to pay more attention to your health, undergo regular checkups, maintain a healthy diet, and manage stress during pregnancy.